Toksoplasmosis Kehamilan - Sinta Maharani; Ika Restu Kaeksi; Nisa Wahyuningsih; Mega Kurnia Mutiara; Liss Dyah Dewi Arini (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Toxoplasmosis is caused by the protozoa Toxoplasma gondii. It often occurs in newborns, who are infected in the womb. Toxoplasmosis in pregnant women will experience abortion, intrauterine fetal death, if the baby survives due to active infection can occur by serious central nervous system defects and can cause mental retardation. Toxoplasmosis in pregnancy causes transmission of toxoplasma gondii through the uteroplacental circulation to the fetus. Laboratory tests performed are anti-toxoplasma IgG and IgM, and anti-Toxoplasma IgG avidity. These tests need to be performed on mothers suspected of being infected with Toxoplasma gondii before or during pregnancy, as well as on newborns from mothers infected with toxoplasma gondii. Spiramycin is given to women suspected of having acute toxoplasma infection in the first trimester or early second trimester, and will be given until delivery. For pregnant women who are likely to have a high infection or have had an infection in the fetus, treatment with spiramycin should be assisted after 18 weeks of pregnancy with pyrimethamine, sulfadiazine, and folic acid. Therefore, pregnant women should be prevented from toxoplasma infection or given treatment as early as possible.